Auditors' Perceptions of Artificial Intelligence, Institutional Pressure, and Auditor Personality on Audit Quality - Abiyyu, Achmad Daffa; Mustafida, Nurul (InFestasi, 2024)
This study analyses the effect of Artificial Intelligence, institutional pressure, and auditor personality on audit quality. The respondents were 84 auditors at Public Accounting Firms in Surabaya. This research is motivated by the inconsistency of previous research results. In addition, AI, which has begun commonly used by auditors to assist in audit tasks, has become the focus of new research. Auditors' perceptions may differ in accepting that AI will provide benefits or cause disruption during the audit process. Empirical results show that institutional pressure and auditor personality influence audit quality, while the use of AI does not affect audit quality. Although AI can help answer various questions, it's not always directly correlated with audit quality. This research show that managers at public accounting firms need to consider the presence of AI to increase the speed and quality of auditor work. However, they also need to organize and plan AI adoption to avoid unsatisfactory results. In addition, managers must also choose skilled professional auditors who can integrate with AI systems to improve company performance and reduce the risk of misuse of AI systems. In practice, managers still really need to consider personality in the auditor profession and use it as an indicator for assessing quality. In addition, auditors' perception of institutional pressure will improve audit quality if they perceive such pressure as a driving factor for performance quality.